"It makes me what I am" an interpretative phenomenological investigation of the social-emotional world of an adolescent with Asperger's syndrome - Grecia, Anthony (Philippine Journal of Psychology, 2011)
This study focused on the social-emotional world of an adolescent with Asperger's syndrome using interpretative phenomenological analysis.